Purification and characterization of fructosyltransferase for the synthesis of short-chain fructo-oligosaccharides and investigation into thier anti-carcinogenic properties - Nemukula, Aluwani (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2009)
There is a growing attention in the synthesis of fructo-oligosaccharides (FOS) due to their excellent bio-functional and health-promoting properties. The current production processes are limited to chemical hydrolysis reactions of plant extracts, which are often associated with several drawbacks. In this study, fructosyltransferase (FTase) and polygalacturonase (PGase) activities, present in a commercial enzyme preparation (PectinexÂ® Ultra SP-L) sourced from Aspergillus aculeatus, have been separated and fully purified by anion-exchange and sizeexclusion chromatography. The FTase possesses fructosyl transfer activity for FOS synthesis and the PGase has pectin hydrolytic activity. Fructosyltransferase is a single-band protein with a molecular weight of 85 kDa, whereas PGase is a distinct protein of 40 kDa. The temperature and pH optima of FTase were 60 ÂºC and 6.0, with a half-life of 8 h; while that for PGase were 40 ÂºC and 6.0, respectively. FTase was slightly inhibited in the presence of NiÂ²â º, MgÂ²â º and urea; but PGase was more susceptible to divalent ions such as CaÂ²â º, MgÂ²â º and MnÂ²â º. The kinetic parameters (Km and Vmax) of FTase for the hydrolysis of Î²-(2â†’1) linkages from sucrose were 752.3 mM and 120.5 Î¼mol.minâ »Â¹.mLâ »Â¹, respectively; whereas the same parameters for pectin hydrolysis by PGase were 13.0 mg.mLâ »Â¹ and 263 Î¼mol.min-1.mLâ »Â¹, respectively. The purified FTase was able to transfer fructosyl residues from sucrose, synthesizing the corresponding chains of FOS. PGase was relatively stable at 40 ÂºC (tÂ½ > 3 h), depolymerizing the pectin backbone while releasing the inulins from within the chicory roots. Analysis of various mixtures of FOS by mass spectrometry, HPLC and Â¹H-NMR was undertaken. Results indicated that MS with electrospray ionization and Â¹H-NMR are capable of providing relative quantitative data of the FOS present in the mixtures. The pharmaceutical effects of various sc-FOS (0.5%, v/v) and SCFA (0.3%, v/v) on certain bacterial enzymes (Î²-glucuronidase, urease and Î²-glucosidase) associated with the formation of carcinogens were also studied. These enzyme activities were not directly influenced by the sc-FOS, but were found to be remarkably decreased by SCFA, pointing toward the prebiotic effect of FOS in intestinal microflora modulation.
Keywords: Oligosaccharides; Polygalacturonase; Aspergillus; Fructose; Inulin; Cancer -- Prevention; Cancer -- Research; Carcinogens; High performance liquid chromatography